Yield and economics of carrot [Daucus carota (L.)] genotypes as affected by water management and Gibberellic Acid in a changing climate - Umar, A.H.; Shittu, E.A. (ADAN JOURNAL OF AGRICULTURE, 2025)
Carrot is a high-value crop, but its productivity and profitability depend on water management, genotype selection, and plant growth regulators like gibberellic acid (GA₃ ). This study examined the interactive effects of these factors on carrot yield and economic returns at two locations: Research and Teaching farm of Bayero University Kano (BUK) and a community demonstration farm at Maida during the 2019/2020 and 2020/2021 cold dry seasons. A split-plot design was used, testing four irrigation intervals (farmer’s practice, 5, 7, and 9 days), two genotypes (Touchon Mega and Griffaton), and four GA₃ application rates (100 ppm applied once, twice, or three times, and a control). Results showed that frequent irrigation (farmer’s practice, W1) and the 5-day interval (W2) significantly improved yield, net income, and benefitcost ratio (BCR) at both locations (P < 0.001). The highest yield was recorded under W1V1G1 at BUK (23,417 kg/ha) and Maida (23,183 kg/ha), with net incomes of ₦6,161,001 and ₦6,183,732, respectively, and a BCR exceeding 6.0. In contrast, the 9-day interval (W4) led to severe yield reductions and financial losses, with the lowest net income observed under W4V2G4 at Maida (₦227,900, BCR 0.18) and BUK (₦277,000, BCR 0.24). Touchon Mega (V1) consistently outperformed Griffaton (V2), confirming its suitability for high-yield, high-profitability carrot farming. Similarly, GA₃ application (100 ppm × 3) significantly enhanced yield and economic returns, while the control (no GA₃) had the lowest profitability. The study concluded that integrating optimized irrigation, superior genotype selection, and GA₃ application maximizes both productivity and financial sustainability in carrot production.